2007
DOI: 10.1007/s10529-007-9351-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression in Escherichia coli and purification of bioactive antibacterial peptide ABP-CM4 from the Chinese silk worm, Bombyx mori

Abstract: The antibacterial peptide CM4 (ABP-CM4), isolated from Chinese Bombys mori, is a 35-residue cationic, amphipathic alpha-helical peptide that exhibits a broad range of antimicrobial activity. To explore a new approach for the expression of ABP-CM4 in E. coli, the gene ABP-CM4, obtained by recursive PCR (rPCR), was cloned into the vector pET32a to construct a fusion expression plasmid. The fusion protein Trx-CM4 was expressed in soluble form, purified by Ni(2+)-chelating chromatography, and cleaved by formic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Two foreign gene expression systems in Escherichia coli were adopted to procure a sizeable amount of moricin to facilitate further studies [15]. In addition, Li et al isolated a 35-residue cationic, amphipathic α-helical peptide, named CM4 (ABP-CM4) from silkworm, and this peptide exhibited broad-spectrum antimicrobial activity [16]. Interestinly, recombinant CM4 also showed antimicrobial activity against E. coli, Penicillium chrysogenum, Aspergillus niger and Gibberella saubinetii [16].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Two foreign gene expression systems in Escherichia coli were adopted to procure a sizeable amount of moricin to facilitate further studies [15]. In addition, Li et al isolated a 35-residue cationic, amphipathic α-helical peptide, named CM4 (ABP-CM4) from silkworm, and this peptide exhibited broad-spectrum antimicrobial activity [16]. Interestinly, recombinant CM4 also showed antimicrobial activity against E. coli, Penicillium chrysogenum, Aspergillus niger and Gibberella saubinetii [16].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…In fact, it was reported that the solubility of foreign proteins was increased by using of Trx as a gene fusion partner. The use of a Trx fusion partner has been successfully applied to expression of many foreign proteins in soluble form including antibacterial peptide ABP-CM4 [15], FNII-2 [16], and arginyl-tRNA synthetase [17]. So, here, we put the Trx structure at the N-terminus of the rhLeptin; and then we expressed rhLeptin as Trx-fusion forms in E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…2 Mulberry silkworm (B. mori) has been reared for longtime in many regions of Thailand especially the Northeast. 3 Reports on the various pharmacological activities of the silkworm have been accumulated such as antioxidant, 4 anticancer, 5 antibacterial, 6 antiviral, 7 antihypertensive, 8 and hepatoprotective activities. 9 Type 2 diabetes is a chronic disease with the mechanisms potentially linked to overweight and obesity.…”
Section: Introductionmentioning
confidence: 99%